Bioorthogonal labeling reveals different expression of glycans in mouse hippocampal neuron cultures during their development - Costa, Diana Pereira Soares (2020)
The following are available online. Scheme S1: Synthesis of peracetylated azidomannose (Ac4ManNAz); Scheme S2: Alternative synthesis of GlcNAz using chloroacetic anhydride and NaOH as a base; Scheme S3: Synthesis of peracetylated azidofucose (Ac4FucAz); Figure S1: 1H-NMR spectra of ManNAz (D2O, 300 MHz); Figure S2: 1H-NMR spectra of Ac4ManNAz (CDCl3 , 300 MHz), mixture of anomers; Figure S3: HPLC chromatogram of purified Ac4ManNAz showing the two anomers; Figure S4: 1H-NMR spectra of GlcNAz (D2O, 300MHz); Figure S5: 1H-NMR spectra of Ac4GlcNAz (CDCl3 , 300 MHz), mixture of anomers; Figure S6: HPLC chromatogram of purified Ac4GlcNAz showing the two anomers; Figure S7: 1H-NMR spectra of 6-azido-1,2,3,4-tetra-O-acetyl-6-deoxy-α,β-L-galactopyranose Ac4FucAz (CDCl3 , 300 MHz): mixture of anomers; Table S1: Primer sequences used in qRT-PCR.